Preparation and evaluation of lactic acid acylated exenatide and its long-acting preparation. (26th November 2019) - Wang, Aiping; Yan, Xiuju; Liang, Rongcai; Wang, Linlin; Chu, Liuxiang; Sun, Kaoxiang; Fu, Fenghua
Abstract: Exenatide (EX), a glucagon-like peptide-1 receptor agonist, is used to treat diabetes mellitus. However, its short half-life necessitates frequent administration and fluctuations in its plasma concentration may cause adverse effects. Previously, we developed glycolic acid acylated EX, which showed a good glucose-lowering effect. However, the release of lactic acid (LA) acylated exenatide (LA-EX) as an acylated adduct in EX microspheres has not been studied. Here, we investigated the biological properties of LA-EX. Additionally, LA-EX-loaded microspheres were formulated by an emulsion–solvent evaporation method and their in vitro characteristics, in vivo pharmacokinetic properties, and antidiabetic activities were evaluated. Pharmacokinetic studies revealed that the t 1/2 of LA-EX (5.95 h) was 2.3-fold longer than that of EX. The antidiabetic activities of LA-EX in db / db mice were similar to those of EX. LA-EX release from microspheres was fairly well-sustained compared to that of EX microspheres. Additionally, LA-EX-loaded microspheres were more effective in lowering nonfasting blood glucose concentrations than EX microspheres. These findings suggest that LA-EX have the same efficacy as EX and that encapsulating LA-EX into microspheres can achieve better efficacy for the long-term type 2 diabetes mellitus treatment. Graphical Abstract: